Improved Energy Efficient in Wireless Sensor Networks - Tayde Vishal Purushottam (Mathematical Statistician and Engineering Applications, 2022)
Wireless Sensor Networks are usually composed of a lot of distributed sensor nodes that organize themselves into a multi-hop wireless network. Several of the main problems in wireless sensor networks are actually energy usage, lack of authentication data integrity as well as instability of road link between sensor nodes which brings down the acceptance of the sensor network. Recently, the present strategies have focused on attaining both security or perhaps energy usage. The study work involves enhanced multipath routing, residual energy based routing, authentication as well as scheduling based approach to create the wireless sensor networks safer with the least energy usage. A brand new Multipath Routing Approach (NMRA) is actually created for raising the energy efficiency in wireless sensor networks. The multipath routing is built to attain higher throughput as well as load balancing. Residual Energy-based Multipath Routing Approach (REMRA) is recommended which attains the integrity as well as minimum residual energy. It utilizes load balancing to stop congestion issues of the network as well as the road stability is actually established based on link price, link bandwidth, and quality of the link.